Estrategias de marketing digital en el Centro de Capacitación Consulting Group del cantón Babahoyo provincia de Los Ríos periodo 2024 - Figueroa Castro, Cristina Javiera (2024)
The study entitled “Estrategias de marketing digital en el centro de capacitación Consulting Group del cantón Babahoyo, provincia de Los Ríos periodo 2024” was designed with the purpose of analyzing the current digital marketing efforts of the organization. In this sense, management attributes and opportunities for improvement of the environment were strategically discussed, the level of perception that users have regarding the training courses was identified and different tactics in digital environments were suggested to strengthen its recognition and positioning in the sector. The research methodology used had a mixed approach with a descriptive non- experimental-cross-sectional design, which facilitated the understanding of the reasons why the training center has not optimally implemented marketing strategies in digital environments. Likewise, a SWOT analysis, a structured interview format directed to the coordinator and a digital questionnaire oriented to 383 residents of Babahoyo were carried out. Through this process, it is highlighted that the absence of knowledge and specialized personnel in the marketing area, the inadequate implementation of strategies in digital channels and the lack of knowledge of consumer preferences are aspects that can weaken the achievement of objectives. Considering the findings, it is suggested the implementation of digital marketing strategies that promote a comprehensive approach to digital platforms, content tactics, strategic collaborations, customer loyalty mechanisms, field studies and the inclusion of indicators to monitor the viability of strategies and make adjustments when appropriate.